Analysis of Understanding Natural Science Concepts on Elementary School Class IV Energy Source Material - Muhammad Nanda Kusuma; Sukardi S; Nora Surmilasari (Indonesian Journal of Primary Education, 2021)
The purpose of this study is to find out the understanding of science concepts in the fourth grade energy source material at elementary school. The research method used in this research is a quantitative description. Data collection techniques in this study were tests, interviews and documentation. The data obtained were then analyzed using percentages. The results of this study indicate that the average understanding of science concepts in the fourth grade energy source material at elementary school belongs to the moderate criteria of 49%. This is evident from the results of the study that the percentage of students' understanding of science concepts from three indicators which include: giving examples and non-examples of a concept by 39% low criteria, classifying objects according to their nature or according to the concept by 63% high criteria and assigning returned a concept by 47% of the moderate criteria.